The Effect of Geogrid Reinforcing Site in Improving Flexible Road Pavement. - نزهه نورشان; بسام سلطان; رامي حنا (Latakia University Journal -Engineering Sciences Series, 2023)
Geosynthetics have been proven to be an ideal element in civil engineering, specifically in the field of pavement. Numerous international research studies have demonstrated the feasibility of using reinforcement in flexible pavement layers, and the clear benefits of this on improving pavement performance. This research focuses on reinforcing road pavements in various locations (aggregate base layer and asphalt cover layer) using biaxial geogrid through experimental laboratory studies. The optimal location for reinforcement is determined by preparing molds of asphalt concrete. A model is then developed for the pavement layers without reinforcement and with reinforcement in the optimal location of the asphalt cover layer and the middle of the aggregate base layer, followed by a plate loading test. The laboratory model is then simulated using the finite element method with the PLAXIS 2D software. The results of the laboratory study revealed the maximum values of the elasticity modulus when reinforcing in the lower third of the sample thickness, as determined by the flexural tension test on the asphalt concrete molds. Additionally, the plate loading test on the laboratory model of the reinforced flexible pavement showed a 41.56% reduction in vertical surface deformations compared to the unreinforced laboratory model. The use of geogrids in the middle of the aggregate base layer and the lower third of the asphalt cover layer significantly reduces vertical deformations, with a reduction of 20.83% in settlement values when reducing the thickness of the layer subbase by 42.86%. The computer modeling also produced similar values to those of the laboratory results, indicating the accuracy of the experimental tests conducted on the model developed in this research.